2010
DOI: 10.1016/j.mcn.2010.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Nervous-tissue-specific elimination of microtubule-actin crosslinking factor 1a results in multiple developmental defects in the mouse brain

Abstract: The microtubule-actin crosslinking factor 1 (MACF1) is a ubiquitous cytoskeletal linker protein with multiple spliced isoforms expressed in different tissues. The MACF1a isoform contains microtubule and actin binding regions and is expressed at high levels in the nervous system. Macf1−/− mice are early embryonic lethal and hence the role of MACF1 in the nervous system could not be determined. We have specifically knocked out MACF1a in the developing mouse nervous system using Cre/loxP technology. Mutant mice d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
92
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(94 citation statements)
references
References 59 publications
2
92
0
Order By: Relevance
“…The MACF1b isoform is highly expressed in the lung, and has been shown to mainly localize to the Golgi in cultured cells (Lin et al, 2005). A novel MACF1c isoform has been described in a conditional knockout study in the nervous system (Goryunov et al, 2010) and was shown to differ from MACF1a by the absence of the N-terminal actin-binding domain. A recent alternative splicing profiling in lung cancer identified another differential splicing isoform within the MT-binding domain of MACF1, which was upregulated in lung cancer cells (Misquitta-Ali et al, 2011).…”
Section: The Various Binding Partners Of Spektraplakinsmentioning
confidence: 99%
See 1 more Smart Citation
“…The MACF1b isoform is highly expressed in the lung, and has been shown to mainly localize to the Golgi in cultured cells (Lin et al, 2005). A novel MACF1c isoform has been described in a conditional knockout study in the nervous system (Goryunov et al, 2010) and was shown to differ from MACF1a by the absence of the N-terminal actin-binding domain. A recent alternative splicing profiling in lung cancer identified another differential splicing isoform within the MT-binding domain of MACF1, which was upregulated in lung cancer cells (Misquitta-Ali et al, 2011).…”
Section: The Various Binding Partners Of Spektraplakinsmentioning
confidence: 99%
“…MACF1 is also important in nervous system development (Goryunov et al, 2010). MACF1 depletion in mouse primary cortical neurons caused a variety of defects and a significant decrease in axon length (Sanchez-Soriano et al, 2009).…”
Section: Cellular Function Of Macf1mentioning
confidence: 99%
“…p0015 Surprisingly, no human diseases or conditions have been associated with MACF1/ACF7, but mouse and zebrafish models suggest its involvement in a wide range of developmental processes, ranging from early embryogenesis (Chen et al, 2006;Gupta et al, 2010), cell migration of fibroblasts, or skin stem cells (Wu, Kodama, & Fuchs, 2008;Wu et al, 2011), as well as heart and brain development (Fassett et al, 2013;Goryunov, He, Lin, Leung, & Liem, 2010;Jorgensen et al, 2014;Sánchez-Soriano et al, 2009 First, in vivo work is relatively fast in flies, and it is not unusual that new experimental ideas yield experimental data within a few weeks. Notably, there are no legal requirements, meaning that experiments can be performed straight off the drawing board with little or no need for an extensive ethical approval process.…”
Section: Article In Pressmentioning
confidence: 99%
“…The spectraplakin family comprises BPAG1 and MACF/ACF7 in mammals, Kakapo/Shot in flies and VAB-10 in C. elegans (Roper et al, 2002;Sonnenberg and Liem, 2007). Spectraplakins have roles in cell migration in vivo (Goryunov et al, 2010;Guo et al, 1995) and regulate the cytoskeletal network (Dalpe et al, 1998;Kodama et al, 2003;Sanchez-Soriano et al, 2009). In endodermal cells from the ACF7 knockout mouse, MTs do not grow along actin bundles and are not tethered to the actin cortex, resulting in defective migration in response to wounding.…”
Section: Introductionmentioning
confidence: 99%